Geochronology and metamorphic evolution of the biotite-plagioclase gneisses from the Luanxian Group in eastern Hebei, North China Craton - Zu, Daji; Duan, Zhanzhan; Cui, Wei; Yang, Liqun; Liu, Jia; Tian, Zhiqiang; Zhang, Juquan (Frontiers in Earth Science, 2025)
Previous metamorphic studies in the eastern Hebei terrane have predominantly focused on rocks within gneiss domes and the Saheqiao linear tectonic belt, while the metamorphosed supracrustal rocks of the Luanxian Group in the Lulong-Shuangshanzi supracrustal belt between gneiss domes remain insufficiently investigated, with limited understanding of their metamorphic characteristics and tectonic setting. This study conducts detailed field investigations, petrological observations, phase equilibria modelling, and zircon U–Pb geochronology on biotite-plagioclase gneisses (samples N16-1 and N16-6) from the Sijiaying iron deposit area. Sample N16-1 contains a mineral assemblage dominated by biotite, K-feldspar, plagioclase, quartz, and epidote, with minor muscovite and sphene, where the minimum XAn in plagioclase (0.20) and maximum XTi in biotite (0.102) constrain peak metamorphic conditions to ∼7.4 kbar/586°C in the phase diagram. Chemical composition zoning with increasing XTi from core to rim in biotite indicates a pre-peak P–T increase process. Sample N16-6 exhibits a mineral assemblage of biotite, plagioclase, K-feldspar, muscovite, and quartz, with epidote and albite occurring as inclusions in biotite, where peak P–T conditions of ∼7.0 kbar/630°C are defined by XAn (0.174) in plagioclase and XTi (0.104) in biotite. Post-peak decompression-cooling is defined by decreasing XTi from core to rim in matrix biotite, collectively defining a clockwise P–T path. Whole-rock geochemical data suggest that the protoliths of the metamorphic supracrustal rocks are pelite and/or greywacke. LA-ICP-MS zircon U–Pb dating yields weighted mean 207Pb/206Pb ages of 2,547 ± 14 Ma (MSWD = 0.32) and 2,555 ± 14 Ma (MSWD = 0.30) for samples N16-1 and N16-6, respectively. The age of ∼2.55 Ga is considered as the maximum depositional timing of supracrustal protoliths, synchronous with TTG gneiss magmatism and regional amphibolite-facies metamorphism. Integrating previous studies with the geological observations of “dome-and-keel” architecture, near-synchronous magmatism, sedimentation, and metamorphism, as well as characteristic P–T paths, we propose that the eastern Hebei terrane was dominated by a vertical tectonic regime during the Neoarchean.